# Math Help Please?

Simplify (2x^2 - 5x + 1)(3x - 1)

### 4 Answers

Relevance

- Iggy RockoLv 74 weeks ago
Use the distributive property.

(2x^2 - 5x + 1)(3x - 1) =

2x^2(3x) - 5x(3x) + 1(3x) + 2x^2(-1) - 5x(-1) + 1(-1) =

6x^3 - 15x^2 + 3x - 2x^2 + 5x - 1 =

6x^3 - 17x^2 + 8x - 1

- ted sLv 74 weeks ago
the Distributive property yields (2x²)(3x) + (2x²)(-1) - (5x)(3x) - ( 5x)(-1) + (1) (3x) + (1)(-1) = 6 x³- 2x² - 15 x² + 5x + 3x - 1 = 6 x³ - 17 x² + 8x - 1

- 4 weeks ago
PEMDAS Parenthesis first, then exponent. Then multiply, then divide. Add. Then subtract. 2x^2 is 4x. All the numbers with x are just equaling the solution plus x. They're all x.

Still have questions? Get your answers by asking now.